Investigation of illicit pregabalin in seized samples from Saudi Arabia - Alamri, Fatimah M.; Alshmmari, Sultan K.; Altamimy, Monerah A.; Al Othaim, Ibrahim A.; Alshehri, Yahya M.; Alafraa, Rayed M.; Almalki, Ahmed D.; Alkhalifah, Turki A.; Sahlabji, Taher; Idris, Abubakr M.; Al-Hamoud, Haitham; Jamous, Yahya F.; et al. (Frontiers in Chemistry, 2025)
IntroductionPregabalin (PGL) is a medication that is prescribed for controlling specific neurological-related symptoms. Due to its abuse in multiple countries, PGL has been classified as a controlled substance by authorities, including the Saudi Food and Drug Authority (SFDA).MethodsThis study developed a validated ultra-performance liquid chromatography-photodiode array detector (UPLC-PDA) method to quantify PGL in 40 seized samples (35 capsules, 5 powders). A complementary liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was used to detect potential adulterants.ResultsThe UPLC-PDA method demonstrated linearity (r = 0.9973) for PGL quantification (0.50–3.00 mg/mL), with an accuracy of 96%–102%. The RSD% values were 0.63% and 1.03% for intra-day and inter-day precision, respectively. Analysis of the five powder samples revealed a relative inconsistency in PGL content (107.91%–114.55%). Moreover, it showed higher variability in PGL content (RSD 1.16%–5.30%), suggesting possible adulteration or poor manufacturing. Furthermore, the results of the nuclear magnetic resonance (NMR) showed an acceptable purity for the powder samples. On the other hand, among 35 capsules, 5 (14.29%) exceeded pharmacopeial limits (95%–105% PGL content), while 6 (17.14%) contained <95% PGL.DiscussionThese results demonstrate significant variability in PGL content and the presence of adulterants, underscoring the need for robust analytical methods in forensic chemistry. Furthermore, the LC-MS/MS method detected adulteration of PGL with codeine, paracetamol, and gabapentin in 2.9% of the analyzed capsules, suggesting custom mixing by perpetrators. In general, 31.43% of these samples failed to meet quality standards and contained substances beyond declared contents that posed toxicity risks, revealing inadequacies in illicit drug production and circulation. The UPLC-PDA method offers a rapid, validated approach for PGL quantification, while LC-MS/MS enhances adulterant detection, supporting forensic and quality control applications.